2007
DOI: 10.1111/j.1365-2133.2007.07883.x
|View full text |Cite
|
Sign up to set email alerts
|

Miconazole as adjuvant therapy for oral lichen planus: a double-blind randomized controlled trial

Abstract: Summary Background  Topical steroids are the first choice for the treatment of oral lichen planus (OLP). Antifungal drugs are often employed together with them, to prevent secondary oral candidosis, although it has been suggested anecdotally that they can also be beneficial for OLP itself. Objectives  To compare the effect of clobetasol propionate with and without a topical antifungal drug (miconazole) on the symptoms and extension of OLP. Methods  A randomized, parallel, double‐blind trial was conducted at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
1
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 15 publications
7
43
1
7
Order By: Relevance
“…Few studies [3,17,21,[24][25][26]33,37] found a statistically significant difference in clinical improvement favouring their respective active interventions when compared to placebo. No statistically significant clinical improvement in the intervention groups when compared to placebo was noted by few other studies [18,19,30]. Sawaarn has recorded the overall treatment response and not the clinical area [32].…”
Section: Effects Of Interventions Active Intervention Vs Placebomentioning
confidence: 99%
See 4 more Smart Citations
“…Few studies [3,17,21,[24][25][26]33,37] found a statistically significant difference in clinical improvement favouring their respective active interventions when compared to placebo. No statistically significant clinical improvement in the intervention groups when compared to placebo was noted by few other studies [18,19,30]. Sawaarn has recorded the overall treatment response and not the clinical area [32].…”
Section: Effects Of Interventions Active Intervention Vs Placebomentioning
confidence: 99%
“…There was no evidence of difference in mean pain score after treatment between active intervention & placebo in three trials [18,19,30]. A statistically significant reduction in mean pain score favouring the active intervention was seen in the remaining nine trials [3,17,21,[24][25][26]32,33,37].…”
Section: Effects Of Interventions Active Intervention Vs Placebomentioning
confidence: 99%
See 3 more Smart Citations